Anemia and heart failure: a cause of progression or only a consequence? - Livio Dei Cas; Rossella Danesi; Giulia Verzura; Alberto Saporetti; Carlo Lombardi; Benedetta Fontanella; Silvia Bugatti; Tania Bordonali; Savina Nodari; Marco Metra (Heart International, 2007)
Anemia is one of the most frequent co-morbidities in the patients with heart failure. Its prevalence increases from 4-7% in the subjects with asymptomatic left ventricular dysfunction to >30% in the patients with severe heart failure. Renal insufficiency, activation of inflammatory mediators, and treatment with renin-angiotensin antagonists seem to be its main determinants. The results of many studies agree in showing that anemia is a powerful independent determinant of survival in patients with heart failure. However, the mechanisms of this relation are still incompletely understood. Moreover a favourable effect on prognosis of the correction of anemia has not been shown, yet, and also controlled studies assessing its effects on exercise tolerance have yielded controversial results. (Heart International 2007; 3: 1-11)